Effect of Hydrophobic Surface on Thermoelectric Cooling-Based Atmospheric Water Generator - Irfan, Abdillah; Kurniawan, Andre; K, Arwizet; Fernanda, Yolli (Jurnal Vokasi Mekanika (VoMek), 2025)
Water has a very important role in everyday life. Apart from humans, other living things also depend on water to survive. But there are still many areas in the world even in Indonesia still experiencing drought or clean water crisis. Therefore, new innovations are needed in producing water. One of the innovations is the atmospheric water generator (AWG) which utilizes the formation of water from air or condensation. The AWG in this research uses thermoelectricity as a cold source. Where thermoelectricity is less noisy, easy to obtain and assemble into a system, has a long service life without requiring maintenance. But thermoelectrics have disadvantages where cooling on thermoelectrics is less efficient. So to overcome this, I as the author use a hydrophobic surface as a condensation surface where it can accelerate condensation and increase the amount of water produced. In this study to see the comparison, tests were carried out using various types and surface areas.